Answer:
The answer is (a, 0)
Step-by-step explanation:
It's correct.
Answer:
Vanessa is 60 and the other person is 12
Step-by-step explanation:
X + 5x = 72
6x = 72
x = 12
12 x 5 = 60
vanessa is 60
the other person is 12
60 + 12 = 72
There is not alot information to answer the question.
Ok, first put in the -2 for each b. That gives:
|-4(-2)-8|+|-1(-(-2))^2|+2(-2)^3
Let's do each section.
The first section is |-4(-2)-8)|
-4 times -2 is 8, minus 8 is 0. The absolute value of 0 is still 0.
Now we move on to |-1(-(-2))^2)|
First we do exponents
-(-2) is 2, and 2^2 is 4. 4 times -1 is -4. The absolute value of -4 is 4
Now the last section, 2(-2)^3
Exponents first: (-2)^3 is -2 * -2 * -2, which is -8.
-8*2=-16.
0+4+(-16)=-12